2013
DOI: 10.4315/0362-028x.jfp-12-273
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Epidemiological Characterization of Antimicrobial-Resistant Escherichia coli Isolates from Japanese Black Beef Cattle

Abstract: We investigated the prevalence of antimicrobial-resistant Escherichia coli in Japanese black beef cattle from the three major production regions of Japan. We collected and examined 291 fecal samples from Japanese black beef cattle in Hokkaido, Chubu, and Kyushu. Of the 3,147 E. coli isolates, 1,397 (44.4%) were resistant to one or more antibiotics; these included 553 (39.8%) of 1,388 isolates from Hokkaido, 352 (54.4%) of 647 isolates from Chubu, and 492 (44.2%) of 1,112 isolates from Kyushu. The difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…However, the amount of veterinary antimicrobial agents (therapeutic and feed additive) sold per food-producing animal weight (pig, broiler, and cattle) in Japan increased from 132 mg kg −1 to 153 mg kg −1 from 2005 to 2010 (25). The use of antibiotics in food animals is increasing, as is the frequency of AMR strains on livestock farms (25, 43, http://www.maff.go.jp/nval/tyosa_kenkyu/taiseiki/index.html). …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the amount of veterinary antimicrobial agents (therapeutic and feed additive) sold per food-producing animal weight (pig, broiler, and cattle) in Japan increased from 132 mg kg −1 to 153 mg kg −1 from 2005 to 2010 (25). The use of antibiotics in food animals is increasing, as is the frequency of AMR strains on livestock farms (25, 43, http://www.maff.go.jp/nval/tyosa_kenkyu/taiseiki/index.html). …”
mentioning
confidence: 99%
“…In 2009, we obtained 3,147 E. coli isolates from the feces of beef cattle on 14 farms in three Japanese regions (Hokkaido, Chubu, and Kyushu) (43) and assessed these isolates for antibiotic resistance. We found that 44.4% (1,347 isolates) of the isolates were AMR, which represented a higher frequency than previously reported (13, 24, 40).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The MLVA was not used to test movement within farms; however, we can assume, based on these results, that the bacterial flora surrounding the calves may play an essential role in the presence of bacteria in their gastrointestinal (GI) tract, which was also observed in a recent study by Liu et al (13). A high prevalence of QREC in feed and water troughs may ease the fecal-oral circulation of QREC, which was also suggested by Yamamoto et al (14) to be important for the on-farm dissemination of multidrug-resistant E. coli. The higher that the proportion of QREC isolates in the calf feed and water troughs is, the more likely it is that QREC establishes itself in the calf gut and the more likely it is that the calf recontaminates the pen environment.…”
Section: Discussionmentioning
confidence: 76%
“…19 Horizontal transferring of resistant bacteria and genes to environment, foods, and other hosts is completely probable. 20 Therefore, tracing AR in commensal microorganisms can help us to adopt strategies for controlling resistance.…”
Section: Discussionmentioning
confidence: 99%